Sustained drug-related reaction with eosinophilia and systemic symptoms (DRESS) triggered by low molecular weight heparins in COVID-19: management and precision diagnosis - Minenna, Elena; Chaoul, Nada; Pia Rossi, Maria; Giliberti, Lucia; Albanesi, Marcello; Nettis, Eustachio; Foschino Barbaro, Maria Pia; Bona, Danilo Di; Caiaffa, Maria Filomena; Macchia, Luigi (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2022)
Low molecular weight heparins (LMWHs), particularly enoxaparin, are administered routinely to Coronavirus disease 2019 (COVID-19) patients, in order to treat or prevent the associated, possibly serious coagulation disorders [1]. Both immunoglobulin E (IgE)-mediated and non IgE-mediated systemic reactions to LMWHs are considered rare [2–4]. Particularly, a single case of the drug-related reaction with eosinophilia and systemic symptoms (DRESS) has been documented in the literature [4]. Here we report on an elderly COVID-19 patient who developed DRESS upon prophylactic treatment with enoxaparin. Etiological diagnosis was corroborated by the lymphocyte proliferation test (LPT) [5] upon recovery. The management strategy adopted is outlined and commented.